Exercise of state power with LGBTIQ+ persons deprived of liberty in Ecuador. Human rights challenges from a Foucauldian perspective. - Narvaez, Juana Lucila; Andrade Gúzman, Carlos (Critical Proposals in Social Work, 2023)
Interview with Juana Narvaez by Carlos Andrade. In this interview we talk with Juana Narvaez, social worker from Ecuador and academic at the University of Cuenca, who shares her reflections on the power exercised by the State with persons deprived of liberty, particularly with LGBTIQ+ persons. LGBTIQ+ persons. In this interview, she shares the results of her research and intervention trajectory and outlines ways forward to improve the conditions of LGBTIQ+ persons. towards improving the living conditions of this population from a human rights perspective.